2021
DOI: 10.1093/nar/gkab667
|View full text |Cite
|
Sign up to set email alerts
|

Genetic depletion of the RNA helicase DDX3 leads to impaired elongation of translating ribosomes triggering co-translational quality control of newly synthesized polypeptides

Abstract: DDX3 is a multifaceted RNA helicase of the DEAD-box family that plays central roles in all aspects of RNA metabolism including translation initiation. Here, we provide evidence that the Leishmania DDX3 ortholog functions in post-initiation steps of translation. We show that genetic depletion of DDX3 slows down ribosome movement resulting in elongation-stalled ribosomes, impaired translation elongation and decreased de novo protein synthesis. We also demonstrate that the essential ribosome recycling factor Rli1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 86 publications
(158 reference statements)
1
13
0
Order By: Relevance
“…While DDX3 affects the global translation landscape, the degree of translation induced varies with individual genes ( 19 , 25 , 33 - 35 ), as revealed by ribosome profiling (also known as ribo-seq) studies ( 36 , 37 ). Indeed, the translation of some mRNAs can be downregulated by DDX3 expression ( 24 , 38 ). In this regard, we highlight recent studies elucidating the role of DDX3 in various types of translation to alter the proteomic landscape in the cell in the presence of diverse intrinsic and extrinsic signals.…”
Section: Ddx3 An Atp-dependent Rna Helicase Of the Dead-box Familymentioning
confidence: 99%
See 4 more Smart Citations
“…While DDX3 affects the global translation landscape, the degree of translation induced varies with individual genes ( 19 , 25 , 33 - 35 ), as revealed by ribosome profiling (also known as ribo-seq) studies ( 36 , 37 ). Indeed, the translation of some mRNAs can be downregulated by DDX3 expression ( 24 , 38 ). In this regard, we highlight recent studies elucidating the role of DDX3 in various types of translation to alter the proteomic landscape in the cell in the presence of diverse intrinsic and extrinsic signals.…”
Section: Ddx3 An Atp-dependent Rna Helicase Of the Dead-box Familymentioning
confidence: 99%
“…Indeed, a recent study of the DDX3 ortholog of Leishmania infantum showed that loss of DDX3 decelerates ribosome movement along the CDS, causing the emergence of elongation-stalled ribosomes and, consequently, reduced protein production ( Fig. 2B ) ( 38 ). Loss of DDX3 in Leishmania also triggered defective recruitment of the ribosome recycling factor ABCE1 and the termination factors eRF3 and GTPBP1, suggesting inefficient ribosome dissociation and recycling in the absence of DDX3 ( 38 ).…”
Section: Translation Regulated By Ddx3mentioning
confidence: 99%
See 3 more Smart Citations